Involvement of MiRNA-211-5p and Arhgap11a Interaction During Osteogenic Differentiation of MC3T3-E1 Cells - Ju, Wenwen; Zhang, Guangfeng; Zhang, Xu; Wang, Jingting; Wu, Tong; Li, Huafeng (Frontiers in Surgery, 2022)
Objective: MicroRNAs (miRNAs) are well-recognized for their abilities to regulate gene expression post-transcriptionally in plants and animals. Recently, miRNA-mRNA regulatory relationships have been confirmed during biological processes including osteogenic differentiation. The aim of this study was to find out more candidate miRNA-mRNA pairs involved in osteogenic differentiation of MC3T3-E1 cells. Methods: A MC3T3-E1-based microarray dataset (accessioned as GSE46400) downloaded from the Gene Expression Omnibus included MC3T3-E1 cells with or without 14-day osteoblast differentiation osteoblast induction. Multiple miRNA-mRNA prediction databases were searched by DEGs to obtained pairs of miRNA-DEG regulatory network. MC3T3-E1 cells were cultured and incubated in the osteogenic differentiation medium for 14 days. The expressions of candidate miRNAs and mRNAs were determined by RT-qPCR in MC3T3-E1 cells. MiRNA-mRNA interactions were verified by dual-luciferase reporter gene assays and experiments using mimics miRNA or their inhibitors. Results: We identified 715 upregulated DEGs and 603 downregulated DEGs between MC3T3-E1 cells with and without osteoblast induction by analyzing the raw data of the GSE46400 dataset. There were 7 overlapped miRNA-mRNA pairs identified during osteogenic differentiation of MC3T3-E1 cells, including mmu-miR-204-5p-Arhgap11a, mmu-miR-211-5p-Arhgap11a, mmu-miR-24-3p-H2afx, mmu-miR-3470b-Chek2, mmu-miR-3470b-Dlgap5, mmu-miR-466b-3p-Chek1, mmu-miR-466c-3p-Chek1. Arhgap11a, H2afx, Chek2, Dlgap5 and Chek1 were hub genes downregulated in MC3T3-E1 cells after osteogenic differentiation, verified by RT-qPCR results. RT-qPCR also determined declined expressions of miR-204-5p and miR-24-3p concomitant with elevated expressions of miR-211-5p, miR-3470b, miR-466b-3p and miR-466c-3p in the MC3T3-E1 cells with osteoblast induction compared with undifferentiated MC3T3-E1 cells. Dual-luciferase reporter gene assays demonstrated Arhgap11a as the target of miR-211-5p. MiR-211-5p upregulation by its mimic increased Arhgap11a expression in MC3T3-E1 cells. Conclusion: Our study characterizes miR-211-5p targeting Arhgap11a promotes the osteogenic differentiation of MC3T3-E1 cells, which provides novel targets to promote osteogenesis process during bone repair.